Prevalence of allergic diseases in individuals with headache - preliminary data from a Brazilian cohort - Dach, Fabiola; Pinheiro, Marcelo de Almeida; Bettiol, Eloisa; Cardoso, Viviane Cunha; Barbieri, Marco Antônio (Headache Medicine, 2024)
Introduction: The first description of the relationship between headaches and allergies dates back to 1927 when Vaughn reported that 36% of patients with migraines had allergic triggers. Another study showed that 58% of individuals with migraines had a history of allergies, and more than 50% of them had a family history of allergic diseases. Since then, contradictory data has been published. Objective: To analyze the prevalence of allergic diseases in individuals with headaches. Verify whether these diseases are associated with headaches, and whether there is an association between these diseases and episodic/chronic headaches. Methods: An analytical and descriptive study from a cohort of live births (1978/79) in Ribeirao Preto/SP. The questions of interest were: 1. The presence and frequency of headache in the last 3 months; 2. The history of medical diagnosis of asthma/bronchitis, allergic rhinitis, skin allergy/eczema, and allergic conjunctivitis. Results: 1775 individuals attended this interview, with an average age of 38.13±0.579, 52.3% of whom were female. Sixty-three percent (n=1113) reported having had a headache in the last three months, with 16.3% of these having chronic headaches. Among patients with headaches, the diagnosis of asthma/bronchitis was reported by 17.80%, allergic rhinitis by 39.35%, skin allergy by 13.32%, and allergic conjunctivitis by 13.84%. There was an association between headache and allergic rhinitis [X2(2)= 27.262, p=<0.001] and headache and allergic conjunctivitis [X2(2)= 7.859, p= 0.017]. No association was observed between headache and asthma/bronchitis [Χ2(1)= 1.008, p= 0.327] or skin allergy [X2(2)= 1.243, p= 0.514]. An association between the presence of episodic headache and a diagnosis of asthma/bronchitis [X2(1)= 4.411, p= 0.043] and a diagnosis of allergic rhinitis [X2(2)= 6.110, p= 0.047 ] was observed. There was no association between episodic/chronic headache and skin allergy [X2(2)= 0.636, p= 0.728} or conjunctivitis [X2(2)= 8.828, p=0.661]. Conclusion: In patients with headaches in the last 3 months, the prevalence of asthma/bronchitis was 17.80%, allergic rhinitis 39.35%, skin allergy 13.32%, and allergic conjunctivitis 13.84%. Patients with headaches had more diagnoses of allergic rhinitis and allergic conjunctivitis. Those with episodic headaches had more diagnoses of asthma/bronchitis and allergic rhinitis when compared to those with chronic headaches.